Определение факторов пульсаций системы подавления мешающих гармоник полупроводникового преобразователя - Панченко, В.В.; Маслий, А.С.; Помазан, Д.П.; Буряковский, С.Г. (Електротехніка і електромеханіка, 2018)
Цель. Целью статьи является определение факторов пульсаций замкнутой системы автоматического регулирования (САР) мешающих гармоник, содержащей полупроводниковый преобразователь с двухсторонней широтноимпульсной модуляцией (ШИМ), а также подтверждение теоретических предпосылок о возможности самокомпенсации действия факторов пульсаций в системе с двухсторонней ШИМ. Методика. Для проведения работы использовались: классическая теория электрических цепей, методы гармонического анализа и теория обобщенных функций. Результаты. Получены выражения, математически связывающие факторы пульсаций, значения коэффициентов демпфирования и регулируемого параметра для разных частот мешающих гармоник в системе с двухсторонней ШИМ. Научная новизна. Экспериментально подтверждены теоретические предпосылки о самокомпенсации действия факторов пульсаций в системе с двухсторонней ШИМ; Практическое значение. Использование результатов работы позволит создать замкнутую САР для эффективного подавления мешающих гармоник в контактной сети постоянного тока. Мета. Метою статті є визначення факторів пульсацій замкнутої системи автоматичного регулювання (САР) заважаючих гармонік, що містить напівпровідниковий перетворювач з двосторонньою широтно-імпульсною модуляцією (ШІМ), а також підтвердження теоретичних передумов про можливість самокомпенсації дії факторів пульсацій в системі з двосторонньою ШІМ. Методика. Для проведення роботи використовувалися: класична теорія електричних кіл, методи гармонійного аналізу і теорія узагальнених функцій. Результати. Отримані вирази, що математично зв'язують фактори пульсацій, значення коефіцієнтів демпфування і регульованого параметра для різних частот заважаючих гармонік в системі з двосторонньою ШІМ. Наукова новизна. Експериментально підтверджені теоретичні передумови про самокомпенсацію дії факторів пульсацій в системі з двосторонньою ШІМ; Практичне значення. Використання результатів роботи дозволить створити замкнуту САР для ефективного придушення заважаючих гармонік в контактній мережі постійного струму. Purpose. The purpose of the paper is to define the pulsation factors of a closed-loop automatic control system (ACS) of interfering harmonics containing a semiconductor converter with double-sided pulse-width modulation (PWM), as well as confirmation of theoretical assumptions about possibilities of self-compensation of pulsation factors’ influence in the system with double-sided PWM. Methodology. The research was conducted with the usage of classic electric circuit theory, frequency analysis methods, generalized function theory. Results. The obtained expressions mathematically relate pulsation factors, value of the damping coefficient and manipulative variable for different frequencies of interfering harmonics in the system with double-sided PWM. The research concerned harmonics with frequencies 100, 300, 600, 900 and 1200 Hz as the most significant constituents of the output voltage of a 12- pulse semiconductor converter. The obtained expressions allow taking into account settings of the selective link and its approximation on the level of supreme frequencies with aperiodic link. Originality. The research has experimentally proved theoretical assumptions about self-compensation of pulsation factors in the system with double-sided PWM. It has been shown that the damping coefficient has a low-impact influence on the values of pulsation factors. It is caused by the pass band of the selective link, which is included in the closed-loop control system of harmonics regulation. Practical value. Application of the research results can contribute to the development of the closed-loop control system for effective attenuation of interfering harmonics in direct current contact wire without interfering in the power part of the semiconductor converter. Besides the possibility to regulate output voltage, it will also help to solve the problem of electromagnetic compatibility of a traction substation semiconductor converter with contact wire. The application of the developed closedloop control system will as well provide for decreasing the size of the filter in the direct current traction substation unit.